Pathogenesis of Periodontal Disease - Contreras, Adolfo (Revista Estomatología, 1992)
Despite of that in the Earth the bacterial species reach a million, only 300-400 species can be detected regulary in samples obtained from subgigival plaque. Probably 10-20 species can play a crucial role in pathogenesis of destructive periodontal diseases. In this review the different factors of microbial virulence implicated in tissue damage and missed fiber attachment and alveolar bone, have been analized. Several. direct virulence factors, such as toxins, enzimes, metabolites, etc; plus the indirect ones bacterial interactions, infection by phages, could activate the humoral and cellular immunity and stimulate the inflamatory response secundarily affecting the Periodontum integrity. Either the direct or indirect pathways accounts for periodontal injury. The full knowledge of pathogenetic mechanisms of periodontitis would improve the development treatment strategies for this important disease.